Decreased RXRα is Associated with Increased β-Catenin/TCF4 in 56Fe-Induced Intestinal Tumors - Suman, Shubhankar; Kumar, Santosh; Fornace, Albert J.; Datta, Kamal (Frontiers in Oncology, 2015)
Although it is known that accumulation of oncogenic β-catenin is critical for intestinal tumorigenesis, the underlying mechanisms have not yet been fully explored. Post-translational β-catenin level is regulated via the adenomatous polyposis coli (APC)-dependent as well as the APC-independent ubiquitin proteasome pathway (UPP). Employing an APC-mutant mouse model (APCMin/+) the present study aimed to investigate the status of RXRα, an APC-independent factor involved in targeting β-catenin to UPP for degradation, in tumor-bearing and tumor-free areas of intestine after exposure to energetic 56Fe ions. APCMin/+ mice were exposed to energetic 56Fe ions (4 or 1.6 Gy) and intestinal tumor samples and tumor-free normal intestinal samples were collected 100 to 110 days after exposure. The status of TCF4, β-catenin, cyclin D1, and RXRα was examined using immunohistochemistry and immunoblots. We observed increased accumulation of the transcription factor TCF4 and its co-activator β-catenin as well as their downstream oncogenic target protein cyclin-D1 in 56Fe-ion induced intestinal tumors. Further, decreased expression of RXRα in tumors as well as in adjacent normal epithelium was indicative of perturbations in β-catenin proteasomal targeting machinery. This indicates that decreased UPP targeting of β-catenin due to downregulation of RXRα can contribute to further accumulation of β-catenin and to 56Fe-induced tumorigenesis.